Learning Design for Understanding the Concepts of Addition and Subtraction for ADHD Students Using the PMRI Approach - Saleha, Atikarani Noer; Putri, Ratu Ilma Indra; Darmawijoyo (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The ability to understand the concept of addition and subtraction is fundamental to all students, including students with Attention Deficit and Hyperactivity Disorder (ADHD). This study aims to produce a learning trajectory for understanding the concept of adding and subtracting whole numbers for students with ADHD using the PMRI approach. The subjects in this study were Grade 1 students with ADHD at the inclusive school or SDN 30 Palembang. The research method used was the design research method. The present research was conducted in three stages, namely the preparation stage, the two-cycle experimental design stage, (cycle I: pilot experiment, cycle II: teaching experiment), and the retrospective analysis stage. Data collection was carried out by an observation, interviews, a pre-test, written tests, documentation, and field notes. The results of the research showed that the learning activities designed could help students understand the concepts of adding and subtracting whole numbers. Some indicators of conceptual understanding that appeared in the students were the students’ abilities to classify objects according to certain characteristics, present concepts in the form of mathematical representations or images, develop the necessary and sufficient conditions for a concept, utilize and choose certain procedures or operations, and apply problem-solving concepts or algorithms. Eventually, a learning trajectory involving two activities using unique contexts of the city of Palembang supports understanding the concept of addition and subtraction.